A COMPARATIVE STUDY OF SUBTITLE VIDEO AND PICTURE SERIES ON STUDENTS’ READING COMPREHENSION OF PROCEDURE TEXT AT HEALTH STUDENTS OF UNIVERSITY OF ADIWANGSA JAMBI - Silvia, Resi (LPPM Universitasdiwangsa Jambi, 2019)
The current study aimed to compare between using subtitle video and picture series in teaching and learning process towards health students? reading comprehension. The research was carried out in 2018-2019 academic year in University of Adiwangsa Jambi, Indonesia. Purposive sampling technique was used to select the sample. One class was selected as sample from first year of nursing program. Totally 36 students were divided into two groups (one experimental group and one control group). Then, a pre-test of reading comprehension was administered to assess the students? reading comprehension. The students of experimental group used video files to improve their reading comprehension while the control group using picture of teaching reading comprehension. In the end of the meeting, all the students were assigned multiple-choice reading comprehension post-test and fulfilled some questionnaires to measure their reading motivation. In order to test the significance between the groups, the independent samples t -test was used. The results of the research showed a significant difference between the students who were learned by using video that was more successful than the students who were learned by using picture. Based on the findings, it indicated that video materials had significant effect on promoting health students? reading comprehension.